2020
DOI: 10.3390/jcm9020605
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Test Assessing MiR663ame and VIMme in Urine Accurately Discriminates Bladder Cancer from Inflammatory Conditions

Abstract: Bladder cancer (BlCa) is a common malignancy with significant morbidity and mortality. Current diagnostic methods are invasive and costly, showing the need for newer biomarkers. Although several epigenetic-based biomarkers have been proposed, their ability to discriminate BlCa from common benign conditions of the urinary tract, especially inflammatory diseases, has not been adequately explored. Herein, we sought to determine whether VIMme and miR663ame might accurately discriminate those two conditions, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…On the one hand, NMIBC is the most frequent BlCa phenotype [35], and disease recurrence is very frequent. Substantial research efforts have been put towards uncovering non-invasive, liquid biopsy-based biomarkers for accurately diagnosing and following-up these patients [36,37]. One major gap in NMIBC relates to patient prognostication and risk stratification after resection, fundamental for establishing the most appropriate follow-up strategy.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, NMIBC is the most frequent BlCa phenotype [35], and disease recurrence is very frequent. Substantial research efforts have been put towards uncovering non-invasive, liquid biopsy-based biomarkers for accurately diagnosing and following-up these patients [36,37]. One major gap in NMIBC relates to patient prognostication and risk stratification after resection, fundamental for establishing the most appropriate follow-up strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial cell carcinomas (UCCs) are the most common form of BlCa, arising along the urinary tract, mostly in the lower tract (bladder and urethra), but also in the Ivyspring International Publisher upper tract (renal pelvis and ureters) [3][4][5][6][7]. The gold-standard diagnostic techniques are mostly invasive and uncomfortable, which led us and others to develop non-invasive tests [8][9][10][11][12][13]. We have previously shown that a biomarker panel (VIM, GDF15 and TMEFF2 promoter methylation) accurately detected both lower and upper tract UCC in urine, and, more recently, that a multiplex panel (VIM and miR663a promoter methylation) accurately discriminated BlCa from inflammatory bladder conditions [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…They found that it was able to diagnose BCa with 80% sensitivity and 88% specificity as well as differentiate low risk patients from healthy controls [ 46 ]. On the other hand, combining only miRNA663 and methylated VIM diagnostic values were slightly inferior, 92.6% sensitivity and 90% NPV [ 141 ].…”
Section: Resultsmentioning
confidence: 99%